If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6z + 19 = 4z + 19 Reorder the terms: 19 + 6z = 4z + 19 Reorder the terms: 19 + 6z = 19 + 4z Add '-19' to each side of the equation. 19 + -19 + 6z = 19 + -19 + 4z Combine like terms: 19 + -19 = 0 0 + 6z = 19 + -19 + 4z 6z = 19 + -19 + 4z Combine like terms: 19 + -19 = 0 6z = 0 + 4z 6z = 4z Solving 6z = 4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4z' to each side of the equation. 6z + -4z = 4z + -4z Combine like terms: 6z + -4z = 2z 2z = 4z + -4z Combine like terms: 4z + -4z = 0 2z = 0 Divide each side by '2'. z = 0 Simplifying z = 0
| -5x-2-10=2-(x+4) | | 85l=685 | | 3(X+1)=2X+24-X | | -3(y-7+3)+3=0 | | 6g+4(g)=1-g | | -x+x=91+7 | | X=-7y-10 | | -2x-6=-2x-4 | | 2.39=x-40 | | 10+9C+5C*2-4+6C= | | a-2-2+15=1+3a | | 49h+20=314 | | -2x-6=-2-4 | | 4p+2+2p+1=8 | | -5x+9=17-x | | 6y=8x-10 | | 10t^2=12t+23 | | C+c=73 | | -3(-4-6y)+7(y+5)= | | 75+2x=0-15 | | 4+x=200 | | 4x^2+4x+32=0 | | 4x+1+3x=-3 | | 2x^2+3+3=-7x | | Y=2x+(-8) | | -15x+9=17-x | | 4X-8=3(2X-4) | | 75+2x=15 | | X+2=2overy-1 | | +t/12=-3 | | -6b+28=9b-2 | | 3x-9=4x-24 |